The hadiths narrated by Hanzalah bin Abi Sufyan in Sahih Al-Bukhari –An analytical study - (Islamic Sciences Journal, 2024)
ABSTRACTPraise be to God, Lord of the Worlds, and may blessings and peace be upon the guide of humanity, and upon all his family and companions.This research came under the title of the hadiths narrated by Hanzalah bin Abi Sufyan in Sahih Al-Bukhari - an analytical study - to show the biography of Imam Al-Bukhari and includes his personal and scientific life, and the biography of the narrator Hanzalah bin Abi Sufyan, including his personal and scientific life, mentioning a number of his sheikhs and students, and the hadiths were mentioned. Which was narrated by Hanzala in Sahih Al-Bukhari, and it is six hadiths. I mention the hadith in its chain of transmission and text, and then I summarize the hadith, then I mention the translation of the narrators of the chain of transmission, and I mention the explanation of the hadith from the books of commentaries, and an explanation of the strange words in the body of the hadiths, then I mention the benefits deduced from the hadiths. The research concluded with a set of results and recommendations.
Keywords: Hadiths, narrated by Hanzalah bin Abi Sufyan, Sahih Al-Bukhari, a hadith that captures knowledge